ANALISIS KONFLIK SOSIAL YANG TERJADI PADA MASYRAKAT MUNA DI KECAMATAN KATOBU KABUPATEN MUNA - Nasruddin Suyuti; La Ode Aris (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2015)
This study is an analysis of the social conflict which happens in Muna society at Katobu District of Muna Regency. The objective of this study was to determine the causes of social conflict and how to handle that social conflicts. This study used a qualitative approach. To get the data field was used several techniques that were observation, interviews, and documentation. The data sources used the primary and secondary data. Primary data is data obtained directly on the object of study or directly to the public, while secondary data is data obtained from documents or the results of studies that have been done by others. These results indicated that the social conflict in Muna society at Katobu caused by several things, such as: conflict of interest between several parties, alcohol consumption, the misunderstanding among youth, as well as acts of planned violence. Keywords: konflik, sosial, masyarakat.